The Non-Obese Diabetic Mouse Strain as a Model to Study CD8+ T Cell Function in Relapsing and Progressive Multiple Sclerosis - Ignatius Arokia Doss, Prenitha Mercy; Roy, Andrée-Pascale; Wang, AiLi; Anderson, Ana Carrizosa; Rangachari, Manu (Frontiers in Immunology, 2015)
Multiple sclerosis (MS) is a neurodegenerative disease resulting from an autoimmune attack on central nervous system myelin. While CD4+ T cell function in MS pathology has been extensively studied, there is also strong evidence that CD8+ T lymphocytes play a key role. Intriguingly, CD8+ T cells accumulate in great numbers in the CNS in progressive MS, a form of the disease that is refractory to current disease-modifying therapies which target the CD4+ T cell response. Here, we discuss the function of CD8+ T cells in experimental autoimmune encephalomyelitis (EAE), a mouse model of MS. In particular, we describe EAE in non-obese diabetic (NOD) background mice, which develop a pattern of disease characterized by multiple attacks and remissions followed by a progressively worsening phase. This is highly reminiscent of the pattern of disease observed in nearly half of MS patients. Particular attention is paid to a newly described transgenic mouse strain (1C6) on the NOD background whose CD4+ and CD8+ T cells are directed against the encephalitogenic peptide MOG[35-55]. Use of this model will give us a more complete picture of the role(s) played by distinct T cell subsets in CNS autoimmunity.